Wolumin mszalny poznańskich karmelitów bosych - Pokora, Piotr (Biblioteka Uniwersytecka w Poznaniu, 2015)
Komunikat prezentuje wolumin mszalny z poznańskiego klasztoru karmelitów bosych z lat 1685–1705 (1738) w oprawie z aksamitu, z okuciami ze srebra, pochodzącej z początku XVIII wieku, a wykonanej zapewne w lokalnym warsztacie introligatorskim.

The communique presents the Roman Missal, the book containing the prescribed prayers, chants, and instructions for the celebration of Mass in the Roman Catholic Church, from the Poznań-based monastery of Discalced Carmelites (Barefoot Carmelites) from the years 1685–1705 (1738). The missal is bound in a velvet binding with silver cornerpieces from the beginning of the eighteenth century and most probably produced in some local bindery.
The Roman missal of the Poznań-based Discalced Carmelites
Keywords: karmelici bosi; The Discalced Carmelites; Poznań; mszał; missal; herb; coat of arms; Archiwum Archidiecezjalne w Gnieźnie; Archdiocese Archive in Gniezno; Biblioteka Katedralna w Gnieźnie; Cathedral Library in Gniezno